Recensiones - J. R. J.; J. M. G.; Ellacuría, Ignacio; I. E.; S. M. A. (ECA: Estudios Centroamericanos, 1970)
No hay resúmenes disponibles. ECA Estudios Centroamericanos, Vol. 25, No. 258, 1970: 155-160.